2022
DOI: 10.1021/acsami.2c13500
|View full text |Cite
|
Sign up to set email alerts
|

Desolvation-Degree-Induced Structural Dynamics in a Rigid Cerium–Organic Framework Exhibiting Tandem Purification of Ethylene from Acetylene and Ethane

Abstract: Due to the industrial requirements for high production and high quality of ethylene, efficient purification of ethylene from acetylene and ethane is of prime importance but challenging. Dynamic metal–organic frameworks (MOFs) have demonstrated intriguing structural dynamics and diverse applications recently. Among them, although a few flexible ones have exhibited interesting ethylene purification capability, rigid ones were yet barely investigated for such purpose. In this regard, a cerium­(III)-based MOF was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Driven by the disparities in the adsorption capacities and binding affinities of the framework to C 2 H 2 , C 2 H 4 , and C 2 H 6 , we further evaluate the separation selectivities for C 2 H 2 /C 2 H 4 and C 2 H 6 /C 2 H 4 with different ratios based on the ideal adsorption solution theory (IAST) (Figure d). For C 2 H 2 /C 2 H 4 (1/99), the selectivity can be up to 2.31 at 1 bar, which is higher than CoMOF-74 (1.70) and MgMOF-74 (2.18), and for C 2 H 2 /C 2 H 4 (50/50), the selectivity can reach 2.47 at 1 bar. , To be more specific, the adsorption selectivities of C 2 H 6 /C 2 H 4 with compositions of 50/50, 10/90, and 1/99 have also been estimated .…”
Section: Resultsmentioning
confidence: 99%
“…Driven by the disparities in the adsorption capacities and binding affinities of the framework to C 2 H 2 , C 2 H 4 , and C 2 H 6 , we further evaluate the separation selectivities for C 2 H 2 /C 2 H 4 and C 2 H 6 /C 2 H 4 with different ratios based on the ideal adsorption solution theory (IAST) (Figure d). For C 2 H 2 /C 2 H 4 (1/99), the selectivity can be up to 2.31 at 1 bar, which is higher than CoMOF-74 (1.70) and MgMOF-74 (2.18), and for C 2 H 2 /C 2 H 4 (50/50), the selectivity can reach 2.47 at 1 bar. , To be more specific, the adsorption selectivities of C 2 H 6 /C 2 H 4 with compositions of 50/50, 10/90, and 1/99 have also been estimated .…”
Section: Resultsmentioning
confidence: 99%
“…The main difference between the two structures is the existence of DMA filled in the channels of the HOF‐NBDA(DMA) framework. Whereas DMA will decompose at high temperature and the resulting Me 2 NH can be removed from the pores by vacuum [41] . Further experiments have been conducted to investigate this possibility.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas DMA will decompose at high temperature and the resulting Me 2 NH can be removed from the pores by vacuum. [41] Further experiments have been conducted to investigate this possibility. As expected, it was found that the powder X-ray diffraction (PXRD) peaks changed obviously and matched well to the HOF-NBDA pattern when the HOF-NBDA-(DMA) sample was activated by heating in air or under vacuum (Figure S6), which indicated a possible solid-state structural transformation.…”
Section: Resultsmentioning
confidence: 99%
“…[4,5] The use of porous solid adsorbent for nonthermally driven purification processes with lower-energy consumption is a promising alternative efficient separation technology. [6][7][8][9][10][11][12][13][14] The separation performance depends on the pore structure and surface property of adsorbent and the physicochemical properties of the adsorbed gases. Compared with zeolite and other porous solid materials, metal−organic frameworks (MOFs) have emerged as viable alternatives with great promise for C 2 H 6 / C 2 H 4 separation owing to their adjustable structures and modulable channel surface functionalization.…”
Section: Doi: 101002/smll202300821mentioning
confidence: 99%